Lexical Diction in Indonesian Pop Song Lyrics by Ebiet G Ade with Environmental Theme - Amin, Mujid Farihul; Gusmiarnum, Genisti Arselia (2023, 2023)
The purpose of this study was to explain the lexical diction contained in the lyrics of the song Do’a Sepasang Petani Muda, Bahasa Matahari, Berita kepada Kawan, Apakah Mungkin, and Nyanyian Burung dan Pepohonan by Ebiet G Ade. In this study, data took the form of song lyrics from the five songs. Qualitative methods are used in this study whose implementation includes three strategic stages, namely data acquisition, data analysis, and presentation of data analysis results. From the results of data analysis, the results showed that the five song lyrics used as the object of the study used lexical diction in the form of synonyms, antonyms, hyponyms, and hypernyms. The purpose of using lexical diction in the form of synonyms, antonyms, hyponyms, and hypernyms is to beautify and give deep meaning related to the intention to be conveyed.